Liver Transplantation and Hepatitis C - Nobuhisa Akamatsu; Yasuhiko Sugawara (International Journal of Hepatology)
Hepatitis-C-virus- (HCV-) related end-stage cirrhosis is the primary indication for liver transplantation in many countries. Unfortunately, however, HCV is not eliminated by transplantation and graft reinfection is universal, resulting in fibrosis, cirrhosis, and finally graft decompensation. The use of poor quality organs, particularly from older donors, has a highly negative impact on the severity of recurrence and patient/graft survival. Although immunosuppressive regimens have a considerable impact on the outcome, the optimal regimen after liver transplantation for HCV-infected patients remains unclear. Disease progression monitoring with protocol biopsy and new noninvasive methods is essential for predicting patient/graft outcome and starting antiviral treatment with the appropriate timing. Antiviral treatment with pegylated interferon and ribavirin is currently considered the most promising regimen with a sustained viral response rate of around 30% to 35%, although the survival benefit of this regimen remains to be investigated. Living-donor liver transplantation is now widely accepted as an established treatment for HCV cirrhosis and the results are equivalent to those of deceased donor liver transplantation.